Insulin Resistance and Leptin Levels in Patients with Obstructive Sleep Apnea - Khosro Sadeghniiat-Haghighi; Mohammad Reza Mohajeri-Tehrani; Ahmad Khajeh-Mehrizi; Zahra Banafsheh Alemohammad; Ania Rahimi-Golkhandan; Sina Hafizi; Bagher Larijani (Journal of Sleep Sciences, 2018)
Abstract